(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was conducted in order to investigate the effect of quantitative and temporal feed restrictions with adding powders of peppermint leaves and organic zinc to the diet for the 2nd and 3rd week on some physiological, immunological and anatomical characteristics of broiler chickens Ross 308 up to 35 days of age. In total, 420 chicks were used, divided into 7 treatments, and each treatment included 3 replicates, with 20 chicks per replicate. The treatments were divided into the control (G1), quantitative feed restriction (40%) only (G2) or with addition of 1% peppermint leaves powder (G3) or with addition of 50 mg/kg of organic zinc powder (G4) and temporal feed restriction (12 hours/ day) only (G5) or with addition of 1% of peppermint leaves powder (G6) or adding 50 mg/kg of organic zinc powder (G7). The results obtained at 21 days of age and as compared with G1 indicated that there was a superiority (p<0.05) of the treatments (G2, G3) and (G4 and G7) in the weight of pancreas and bursa of Fabricius, respectively, superiority (p<0.05) in the most of the feed restrictions was in the relative weight of thymus gland with no significant difference was among the most of treatments in packed cells volume. Also, G3, G4 and G7 recorded a decrease (p< 0.01) in uric acid level , but no significant difference was recorded among G3, G4, G6, G7 and G1 treatment in ALT activity. As compared with G1 at 35 days of age, G3 and G5 surpassed (p<0.05) in lung weight, no significant difference among G2, G5, G6, G7 and G1 was in packed cells volume, a decrease in uric acid level (p< 0.01) was in the most of feed restriction treatments and no significant difference was recorded among feed restriction treatments and G1 in ALT activity. The G3, G4 and G7 had the highest rate (p<0.05) of antibody titers against Gumboro and Newcastle diseases, with no significant differences was among treatments in the absolute length of gut , heterophils/lymphocytes ratio, creatinine level and AST activity in the blood serum. We conclude that the application of feed restriction regimes had a positive role in stabilizing or improving the physiological parameters of blood, anatomical traits and enhancing immunity in broilers, especially in case of supporting the diet with peppermint leaves or organic zinc powder.